(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
This paper examines the impact of prescriptivism on the evolution of past tense forms of irregular English verbs, including "dwell," "smell," "spell," "burn," "spoil," and "learn." The prescriptive approach to grammar, which aims to identify and enforce what are considered to be the correct grammatical forms, was particularly prominent during the eighteenth century. Nevertheless, the century was not wholly prescriptive, with differing interpretations of what constituted a regular and irregular verb. The past tense of regular verbs was typically formed by adding -ed, whereas irregular verbs did not follow this predictable pattern. In light of Anderwald’s research, this study posits that prescriptivism had a constrained effect on these verbs. This paper employs data from eighteenth- and nineteenth-century British fiction to examine the historical evolution of these verb forms. The eighteenth century saw a proliferation of prescriptive grammar books aimed at a linguistically insecure middle class, with grammarians attempting to "fix" the language. However, these prescriptive efforts were often disconnected from actual linguistic changes. This study examines irregular verb usage in British fiction using the software AntConc to analyze texts from both centuries, dividing them into twenty-year segments. The analysis reveals the frequency of different past tense forms, offering insights into the historical variation and the limited prescriptive influence. The findings, supported by detailed data and methodology, contribute to understanding the complex interaction between prescriptive grammar and linguistic evolution.